2016
DOI: 10.1002/ange.201603929
|View full text |Cite
|
Sign up to set email alerts
|

A Powerful Chiral Phosphoric Acid Catalyst for Enantioselective Mukaiyama–Mannich Reactions

Abstract: A new BINOL‐derived chiral phosphoric acid bearing 2,4,6‐trimethyl‐3,5‐dinitrophenyl substituents at the 3,3′‐positions was developed. The utility of this chiral phosphoric acid is demonstrated by a highly enantioselective (ee up to >99 %) and diastereoselective (syn/anti up to >99:1) asymmetric Mukaiyama–Mannich reaction of imines with a wide range of ketene silyl acetals. Moreover, this method was successfully applied to the construction of vicinal tertiary and quaternary stereogenic centers with excel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In the following years, Akiyama's group investigated the scopeo ft his reaction, giving rise to aw ide array of derivatives. [72] In spite of the high yields achieved with dinitrophenyl catalyst derivatives 133 and 134 (see Figure 5), the enantioselectivity was moderate at best and always lower than Akiyama's reportedr esults (see Scheme 45). [72] In spite of the high yields achieved with dinitrophenyl catalyst derivatives 133 and 134 (see Figure 5), the enantioselectivity was moderate at best and always lower than Akiyama's reportedr esults (see Scheme 45).…”
Section: Disulfonimide and Phosphoric Acid Catalystsmentioning
confidence: 83%
See 1 more Smart Citation
“…In the following years, Akiyama's group investigated the scopeo ft his reaction, giving rise to aw ide array of derivatives. [72] In spite of the high yields achieved with dinitrophenyl catalyst derivatives 133 and 134 (see Figure 5), the enantioselectivity was moderate at best and always lower than Akiyama's reportedr esults (see Scheme 45). [72] In spite of the high yields achieved with dinitrophenyl catalyst derivatives 133 and 134 (see Figure 5), the enantioselectivity was moderate at best and always lower than Akiyama's reportedr esults (see Scheme 45).…”
Section: Disulfonimide and Phosphoric Acid Catalystsmentioning
confidence: 83%
“…[71] Following Akiyama's work, Yamamoto and Zhou studied the same reactions in terms of the application of other chiral phosphorica cid derivatives as catalysts by modifying the aromatic substituents at the 3,3'-positions in the catalyst structure ( Figure 5). [72] In spite of the high yields achieved with dinitrophenyl catalyst derivatives 133 and 134 (see Figure 5), the enantioselectivity was moderate at best and always lower than Akiyama's reportedr esults (see Scheme 45). To increaset he enantioselectiv- In their ensuing work, Yamamoto and Zhou rendered the 2hydroxyphenyl moiety in aldimines unnecessaryi no rder to reach good enantioselectivities.…”
Section: Organocatalytic Mukaiyama-mannich Reactions 31 Disulfonimimentioning
confidence: 83%
“… [64] It was previously shown that substrates lacking an OH group in the N−Ph moiety cannot be effectively activated by BINOL‐based chiral phosphoric acids 1 . In contrast, more acidic catalysts, such as N ‐triflylphosphoramides (Scheme 1d) and (trifluoromethyl)sulfonyl methanes (Scheme 1c), provide fast reactivity, good yields and excellent ee values [24,65] …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, more acidic catalysts, such as Ntriflylphosphoramides (Scheme 1d) and (trifluoromethyl)sulfonyl methanes (Scheme 1c), provide fast reactivity, good yields and excellent ee values. [24,65] Given that the free acid 4 is prone to oxidation and hydrolysis, the reactive complex 14 was prepared in situ in a way avoiding the presence of free acid. First imine 13 is mixed with an ethereal solution of HCl (10 mol %) forming the iminium hydrochloride.…”
Section: First Reactivity Testsmentioning
confidence: 99%